2012
DOI: 10.1021/ac302085y
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Leukocytes from Blood Using Spiral Channel with Trapezoid Cross-Section

Abstract: Inertial microfluidics has recently drawn wide attention as an efficient, high-throughput microfluidic cell separation method. However, the achieved separation resolution and throughput, as well as the issues with cell dispersion due to cell-cell interaction, have appeared to be limiting factors in the application of the technique to real-world samples such as blood and other biological fluids. In this paper, we present a novel design of a spiral inertial microfluidic (trapezoidal cross-section) sorter with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
244
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(253 citation statements)
references
References 41 publications
8
244
1
Order By: Relevance
“…8. This translates to a throughput of $3.6 ll/min of whole blood (45% hct) which is comparable to the recent blood sorting work by Han et al 43 where they showed >90% efficiency of enrichment of WBCs. Although platelets could not be separated, there is an almost complete separation of leukocytes and erythrocytes.…”
Section: Blood Cell Sortingsupporting
confidence: 75%
See 2 more Smart Citations
“…8. This translates to a throughput of $3.6 ll/min of whole blood (45% hct) which is comparable to the recent blood sorting work by Han et al 43 where they showed >90% efficiency of enrichment of WBCs. Although platelets could not be separated, there is an almost complete separation of leukocytes and erythrocytes.…”
Section: Blood Cell Sortingsupporting
confidence: 75%
“…Further, since the throughput and efficiency was calculated using only the viable cells collected at the outlets, the throughput is indicative of cell viability. As such blood cells are quite robust as shown in the previous work by Toner et al 1 and Han et al 43 …”
Section: Blood Cell Sortingsupporting
confidence: 61%
See 1 more Smart Citation
“…These forces allow for the precise alignment of particles in a flow at throughputs orders of magnitudes higher than in previous microfluidic technologies. The high throughput nature of inertial focusing has enabled a range of microfluidic technologies for biomedical applications from separation technologies [8][9][10][11][12] , to automated sample preparations 13,14 , to novel cell analysis techniques such as cell deformability cytometry 15 and the isolation of circulating tumor cells from blood 16,17 .It is generally accepted that inertial focusing in straight channels is dependent on two main parameters: Reynolds number, defined as Re C 5 rU Max D h /m, where r is the fluid density, m is the fluid viscosity, U Max > 3/2U Avg is the maximum velocity of the fluid and D h is the hydraulic diameter of the channel defined as D h 5 2hw/(h 1 w) where h and w are the height and width of the channel cross section respectively, and the particle confinement ratio, l 5 a/D h , where a, is the particle size. Prior research has determined a minimum threshold for inertial focusing to occur such that l .…”
mentioning
confidence: 99%
“…These forces allow for the precise alignment of particles in a flow at throughputs orders of magnitudes higher than in previous microfluidic technologies. The high throughput nature of inertial focusing has enabled a range of microfluidic technologies for biomedical applications from separation technologies [8][9][10][11][12] , to automated sample preparations 13,14 , to novel cell analysis techniques such as cell deformability cytometry 15 and the isolation of circulating tumor cells from blood 16,17 .…”
mentioning
confidence: 99%